If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(4+8s)=(2-3s)=3(s+6)
We move all terms to the left:
(4+8s)-((2-3s))=0
We add all the numbers together, and all the variables
(8s+4)-((-3s+2))=0
We get rid of parentheses
8s-((-3s+2))+4=0
We calculate terms in parentheses: -((-3s+2)), so:We get rid of parentheses
(-3s+2)
We get rid of parentheses
-3s+2
Back to the equation:
-(-3s+2)
8s+3s-2+4=0
We add all the numbers together, and all the variables
11s+2=0
We move all terms containing s to the left, all other terms to the right
11s=-2
s=-2/11
s=-2/11
| 11+45=6x-10 | | -13*5+(-7/8x)=-79 | | -5=1+8n-6 | | 90=3y-10+7y | | 653=s-(-591) | | 5x-4.7=8.2 | | -13(5)+(0.875x)=-79 | | 5(x+2)=-4+12 | | (764x2)+12=x | | 653=s−-591 | | r/2+-8=10 | | 90=10y-10 | | 2(4x-3)=-5x+2 | | 7x-12=10x-2 | | 1/2h=2/5+h | | 3h+1=-8 | | 351(xx8)+15=x | | 4.6g+3=1.6g+18 | | d/2+6=9 | | 1/2h=2/5+5 | | 20+3x=-4x-15 | | d/3+9=12 | | -16=3f+-1 | | S+4+2s=47 | | d3+ 9=12 | | 26j=156 | | 24d=144 | | 3w-10=-4 | | m-(-122)=315 | | 4a^2-26a+12=0 | | -3.1x+8=2.9+32 | | m−-122=315 |